Behavioral Factors Influencing Investment Decision of Individual Investor at Nepalese Stock Market - Shrestha, Purna Man (Journal of Entrepreneurship & Management Studies, 2024)
The investment decision of individual investor is influenced by macro/micro economic and behavioral factors. Interest rate, economic growth, inflation, government policy, technological developments, etc., are the macro-economic factors, and firm size, book-to-market equity, cash flow yield, earnings yield, and dividend yield, etc. are the micro-economic factors whereas accounting information, advocate suggestion, personal financial needs, social relevance, self-image/firm-image coincidence, etc. are the behavioral factor. This paper has analyzed the perception of investor on the selected behavioral factors that makes influence on individual investor’s investment decisions at Nepalese stock market. Using the structured survey questionnaire, this study concludes that behavioral factors have significant influence on investment decision of individual investor. This study revealed that to get rich quickly, reputation of the firm, feelings for a firm’s products and services, and firm status in industry are the major influencing Self–image/Firm-image factor. On the other hand, friend or coworker’s recommendations, family member opinion, and broker recommendation are the most significant influencing Advocate Recommendation factors. Similarly, return maximizing, stock marketability, ease of obtaining borrowed funds, and expected dividends are the major Personal Financial Needs factors, and past trends of stock, information of dividend, price level of other stock, and information of the stock market are the major Market Information factors for influencing investment decision of individual investor at Nepalese stock market.